Bud Dormancy in Perennial Fruit Tree Species: A Pivotal Role for Oxidative Cues - Beauvieux, Rémi; Wenden, Bénédicte; Dirlewanger, Elisabeth (Frontiers in Plant Science, 2018)
For perennial plants, bud dormancy is a crucial step as its progression over winter determines the quality of bud break, flowering and fruiting. In the past decades, many studies, based on metabolic, physiological, subcellular, genetic and genomic analyses, have unraveled mechanisms underlying bud dormancy progression. Overall, all the pathways identified are interconnected in a very complex manner. Here, we review early and recent findings on the dormancy processes in buds of temperate fruit trees species including hormonal signaling, the role of plasma membrane, carbohydrate metabolism, mitochondrial respiration and oxidative stress, with an effort to link them together and emphasize the central role of ROS accumulation in the control dormancy progression.